EARLY STAGES OF ARCHAEOLOGICAL STUDY OF THE KASHKADARYA OASIS - Rajabova, Nilufar (Current Research Journal of History, 2021)
The article analyzes the first stages of studying the archaeological sites of the Kashkadarya oasis from a historical point of view. Beginning in the 18th century, Europeans began to record information about the Kashkadarya oasis. Their main focus is on highlighting the lifestyle of the population, as well as information on historical monuments. In particular, in memoirs, reports and brochures, A. Burns, N. Khannykov, V.V. Bartold, N. Maev, V. Krestovsky, B. Litvinov, D. Logofet, A. Validov, I. Kastane, L. Zimin, you can get a lot of information on this topic. Despite this, the first studies were mostly brief. Most importantly, the attention of architects and art critics is focused on the history of architectural structures in Shakhrisabz, built during the reign of Amir Temur and the Temurids. However, attempts to shed light on the history of the cities of Karshi and Shakhrisabz based on written sources consisted in a collection of the first archaeological observations, historical artifacts and manuscripts. Noteworthy is the information written by N. Khannykov, V.V. Bartold, N. Mayev. Subsequent studies also made extensive use of their memoirs. B. Litvinov's information about the Kashkadarya oasis was supplemented by his drawings. According to Logofet, the history of the city of Shakhrisabz is emphasized, and archaeological excavations show that its history goes back two thousand years. Logofet pays great attention to the medieval history of Karshi, cites various historical sources. It is important for I.Kastana and L.Zimin to describe the archaeological monuments preserved in the vicinity of Karshi from the point of view of that period and compare them on the basis of ancient and medieval written sources.